PENGARUH MODAL INTELEKTUAL TERHADAP KINERJA KEUANGAN PERBANKAN DI INDONESIA - Aprilina, Vita (JRAK (Jurnal Riset Akuntansi dan Komputerisasi Akuntansi), 2013)
The purpose of this study is to obtain empirical evidence of the efficiency of value added(VAICTM) with the major components of a firm?s resource base (physical capital, human capitaland structural capital) and dimensions of financial banks performance: capital: CAR, aseetsquality: NPL, earnings: ROA, liquidity: LDR. The population of the study is the listed banks on Indonesia Stock Exchange period 2008until 2010. Determination of the sample in this study is carried out by using the method ofpurposive sampling. The hypotheses are tested using multiple regression analysis. The results show that: intellectual capital is measured from human capital (VAHU)positive significant influential to financial performance with CAR and LDR, negative significantinfluential to financial performance with NPL and ROA, not influential to financial performancewith LDR. Intellectual capital is measured from structural capital (STVA) positive significantinfluential to financial performance with NPL and ROA, negative significant influential tofinancial performance with LDR, not influential to financial performance with CAR. Intellectualcapital is measured from physical capital (VACA) positive significant influential to financialperformance with NPL, negative significant influential to financial performance with CAR andLDR, not influential to financial performance with ROA